Vocational education and training in Luxembourg : short description - (:unkn) unknown (Publications Office of the European Union, 2015)
"Luxembourg's vocational education and training (VET) is highly differentiated. Apprenticeships and school-based VET coexist. While some features may seem similar to those in other countries, taking a closer look is important to understand national concepts and terms. Luxembourg’s education and training system reflects its geographic and socioeconomic context: its small size, the close ties with its neighbours, its multilingual nature and high share of foreign nationals, and the well-established cooperation with social partners. Recently implemented reform has strengthened the links to the labour market and brought about a shift towards competence-based and modular vocational programmes. The implementation of this reform has also revealed weaknesses in the system; evaluation of the reform will provide stakeholders with evidence of a need for further changes. By providing an insight into its main features and highlighting related policy developments and challenges, this short description contributes to better understanding of VET in Luxembourg." It has been published during the Luxembourgian Presidency of the Council of the EU (second half of 2015). (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 4.1 Finanzierungsquellen; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Höhere Berufsbildung; Bildungsfinanzierung; Qualitätssicherung; Luxemburg